Reliable and durable Golgi staining of brain tissue from human autopsies and experimental animals - Rosoklija, Gorazd B; Petrushevski, Vladimir M; Stankov, Aleksandar; Dika, Ani; Jakjovski, Zlatko; Pavlovski, Goran; Davcheva, Natasha; Lipkin, Richard; Schnieder, Tatiana; Scobie, Kimberley; Duma, Aleksej; Dwork, Andrew J (Elsevier BV, 2014)
Golgi stains are notoriously capricious, particularly when applied to human brain. The well-known difficulties, which include complete failure of impregnation, patchy staining, unstable staining, and extensive crystalline deposits in superficial sections, have discouraged many from attempting to use these techniques. A reliable method that produces uniform impregnation in tissue from human autopsies and experimental animals is needed.
Keywords: Golgi-Kopsch; Rapid Golgi; Golgi-Cox; Autopsy; Human; Experimental animals; Dendrites; Dendritic spines